In-Hospital Outcomes and Recurrence of Acute Ischemic Stroke in Patients With Solid Organ Malignancy. (26th July 2022) - Garg, Aayushi; Chopra, Saurav; Starr, Matthew; Rocha, Marcelo; Dawod, Judy; Leira, Enrique; Shaban, Amir
Abstract : Background and Objectives: The aim of this work was to evaluate the influence of solid organ malignancies on the in-hospital outcomes and recurrent strokes among patients hospitalized with acute ischemic stroke (AIS). Methods: Adult hospitalizations with a primary diagnosis of AIS were identified from the Nationwide Readmissions Database from 2016 to 2018. Logistic regression was used to compare the differences in the use of acute stroke interventions and clinical outcomes in patients with and without malignancy. Survival analysis was used to evaluate the risk of readmission due to recurrent stroke after discharge. Results: There were 1, 385, 840 hospitalizations due to AIS (mean ± SD age 70.4 ± 14.0 years, female 50.2%). Of these, 50, 553 (3.7%) had a concurrent diagnosis of solid organ malignancy. The 5 most common malignancies included lung cancer (24.6%), prostate cancer (13.2%), breast cancer (9.3%), pancreatic cancer (6.5%), and colorectal cancer (6.2%). After adjustment for baseline differences, patients with malignancy were more likely to have intraparenchymal hemorrhage (odds ratio [OR] 1.11, 95% CI 1.04–1.19), in-hospital mortality (OR 2.15, 95% CI 2.04–2.28), and discharge disposition other than to home (OR 1.70, 95% CI 1.64–1.75). Patients with malignancy were less likely to receive IV thrombolysis (tissue plasminogen activator [tPA]) and were more likely to undergo mechanical thrombectomy (MT). Among the subgroups of patients treated with tPA or MT, the outcomes were comparable between patients with and without malignancy, except patients with lung cancer remained at a higher risk of mortality and adverse disposition despite these acute stroke interventions. Patients with malignancy were at a higher risk of readmission due to recurrent AIS within 1 year of discharge (hazards ratio 1.18, 95% CI 1.11–1.25), and this risk was driven specifically by the lung and pancreatic cancers. Discussion: While patients with malignancy generally have worse in-hospital outcomes compared to those without, there is considerable variation in these outcomes according to the different cancer types and the use of acute stroke interventions. The use of tPA and MT is generally safe for eligible patients with an underlying malignancy. Patients with lung and pancreatic cancers have a higher early risk of recurrent stroke and might need more intensive surveillance and careful institution of the optimal secondary prevention measures.